PRAKTEK RE-UPLOAD VIDEO OLEH YOUTUBER DAN KEABSAHAN PEMBAYARANNYA (Suatu Tinjauan dari Perspektif Konsep Hak Ibtikar) - Fazlul Rahman (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2019)
Youtube is a video sharing website created by three former Paypal employees in February 2005, this site allows users to upload, watch and share videos. The company is based in San Bruno, California, and uses Adobe Flash Video and HTML5 technology to display a variety of user-made video content, including movie clips, TV clips and music videos. In addition there are also amateur content such as video blogs, short original videos and educational videos. Currently YouTube has provided two types of licenses on its site, namely Copyright frequency (cannot be re-uploaded by other parties) and Creative Commons BY Protection (CC BY) (may be re-uploaded by other parties). Even so it is not a problem without problems, the problems that still occur on Youtube are cases of copyright on the site, such as the practice of re-uploading videos here for example. This study examines how the validity of income obtained from the video re-upload activity on Youtube in terms of the Ibtikar Rights Perspective in Islam and Muamalah Fiqh. This thesis research includes the type of library research, which is data collection using study studies of books, journals, printed documents, and from sites on the internet. The results of the research conducted by the author in this thesis are unlawful in the practice of re-uploading videos that are carried out solely to obtain personal gain without giving royalties to the relevant producer / label, in other words the act is the same as a trader selling people's property otherwise without the permission of the owner or selling stolen goods, this is clearly detrimental to the creator or copyright holder because the video circulating on youtube is not given permission by the video creator to spread the creation to the public using the Youtube website. In Islam, copyright is known as Haq Ibtikar, namely a special right attached to the original video owner and part of intellectual property, both material and immaterial, so that it must be protected by law. Islam highly respects copyright as a private property right so that the right to ibtikar is classified into the Maqashid Sharia to maintain the existence of ownership of the assets of every Muslim. Every treasure that results from a video re-upload in Islam and Muamalah Fiqh is unlawful, because it is included in violating the rights of others in a vanity.